Effectiveness of 4-week alternate-day fasting on body mass and body composition in Asia males with BMI ≥ 23 kg/m2 - Tan, Gerald Zheng Yang (2019)
Background: Alternate – day fasting (ADF) has shown to induce weight loss and improve body composition. While most researches looked at longer duration ADF (>8 weeks), comparatively fewer have looked into short-term ADF. Furthermore, shortest duration to observe a significant weight loss is not well-established. Purpose: To investigate the effectiveness of 4-weeks ADF on body mass and body composition in Asian males with body mass index (BMI) of ≥ 23kg/m2, and to determine how fast can significant body mass loss be observed. Methods: 24 males (age: 24.8 ± 1.6 years) with BMI ≥ 23kg/m2 were required to alternate between fasting day (400-600kcal) and feeding day (ad libitum) for four weeks. Five laboratory sessions (baseline + four weekly measurement during ADF) were mandated. Body mass, height, physical activity level and adherence rate were measured in every session while body composition was measured during the first and last session. Thereafter, a paired t-test and one-way repeated measures ANOVA were performed to note for significant differences. Results: Significant reduction was observed in pre-post analysis of body mass (2.63 ± 0.35kg), BMI (0.86 ± 0.11kg/m2), fat mass (2.02 ± 0.26kg), fat free mass (0.68 ± 0.25kg) and percentage body fat (1.72 ± 0.3%) (p < .05). Weekly body mass was found to be significantly reduced just after 1 week (p < .001) from baseline. Conclusion: 4-weeks ADF is sufficient to reduce body mass and improve body composition amongst Asian males with BMI ≥ 23kg/m2. Also, 1 week of ADF can elicit significant body mass loss.